Teaching Prolog techniques - Brna, Paul (1991)
Abstract: "Learning Prolog (or any other programming language) requires the student to relate the behaviour of code to its structure. We outline work on the development of an approach to helping students learn Prolog via Prolog programming techniques. After introducing the notion of programming techniques we sketch the reasons why they are of potential interest in teaching students to program. We describe some preliminary work on the development of a Prolog Techniques editor. Although this tool has not yet been used with students we anticipate a number of problems in learning to use it."
Keywords: Computer software; Education and training; Computer programming; Prolog (Computer program language)